Effect of Reducing Field of View on Multidetector Quantitative Computed Tomography Parameters of Airway Wall Thickness in Asthma. Issue 4 (July 2015) - Sheshadri, Ajay; Rodriguez, Alfonso; Chen, Ryan; Kozlowski, James; Burgdorf, Dana; Koch, Tammy; Tarsi, Jaime; Schutz, Rebecca; Wilson, Brad; Schechtman, Kenneth; Leader, Joseph K.; Hoffman, Eric A.; et al.
<x xml:space="preserve">Abstract</x> Objective We reduced the computed tomography (CT)–reconstructed field of view (FOV), increasing pixel density across airway structures and reducing partial volume effects, to determine whether this would improve accuracy of airway wall thickness quantification. Methods We performed CT imaging on a lung phantom and 29 participants. Images were reconstructed at 30-, 15-, and 10-cm FOV using a medium-smooth kernel. Cross-sectional airway dimensions were compared at each FOV with repeated-measures analysis of variance. Results Phantom measurements were more accurate when FOV decreased from 30 to 15 cm (P < 0.05). Decreasing FOV further to 10 cm did not significantly improve accuracy. Human airway measurements similarly decreased by decreasing FOV (P < 0.001). Percent changes in all measurements when reducing FOV from 30 to 15 cm were less than 3%. Conclusions Airway measurements at 30-cm FOV are near the limits of CT resolution using a medium-smooth kernel. Reducing reconstructed FOV would minimally increase sensitivity to detect differences in airway dimensions.